A new Agave species (Asparagaceae, Agavoideae), from southern Oaxaca, Mexico - Starr, Greg D. (Phytotaxa, 2020)
A new species, Agave calciphila, endemic to the limestone hills north of Nizanda, Oaxaca, Mexico, is described. Its vegetative and flower morphology place this species in the section Heteracanthae, and close to Agave angustiarum, A. ghiesbreghtii, and A. huehueteca. After a comparison with these three species, A. calciphila was found to have shorter sterile peduncle and flowers.